Effect Of Cognitive-Behavioral Therapy on Depression in Chronic Kidney Disease Patients Undergoing Hemodialysis - Nur Azizah AS; Khairina; Artaria Tjempakasari; Khadijah Khairul Bariyah (Faculty of Medicine, Universitas Airlangga, 2024)
Introduction: Depression is the most common psychiatric disorder suffered by patients with chronic kidney disease who are undergoing hemodialis. Depression can lead to decreased quality of life and increase the economic burden on the health system. CBT is a validated treatment for depression, and there has been no research yet on CBT in patients with chronic kidney disease undergoing hemodialysis in RSUD, Dr. Soetomo Surabaya. To prove the effect of CBT on the improvement of depression in patients with chronic kidney disease undergoing hemodialysis in RSUD, Dr. Soetomo Surabaya. Methods: Experimental study with use of randomized, pretest-posttest control group design. Respondents meeting the criteria were divided by random allocation, treatment by CBT for as many as 17 respondents, and even as much control as 20 respondents. The mean age of the treatment group was 37.24 and the control group was 44.45, with a range of 21–60 years old, who experienced mild and moderate depression without antidepressants. Treatment consists of 4 sessions, 45 minutes each session, once a week. Effectiveness was measured using BDI instruments. Results: There were significant differences in pre- and post-depression scores in the treatment group (p = 0.007), and there were significant differences in depression improvement between the treatment and control groups (p = 0.006). Depression improvement in the treatment group was 64.7% compared to the control group’s 25.0%. Conclusion: CBT can improve mild and moderate depression without antidepressants (NNT = 3) in patients with chronic kidney disease undergoing hemodialysis treatment at RSUD Dr. Soetomo Surabaya.